IMPLEMENTASI DANA KANYAAH DI RT 05 KELURAHAN SUKAMULYA : MEMBANGUN SOLIDARITAS ANTAR AGAMA MELALUI PEMBIAYAAN KESEHATAN DAN PEMAKAMAN - Nur, Alfiyah Intan; Putra, Vedu Pamungkas; Amalia, Via; Sintia Ari, Ni Made Reniska; Hasibuan, Kobul Baringin; Aziz, Rohmanur (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2024)
This study aims to determine the implementation of the kanyaah fund in RT 05 Sukamulya Village which is one of the programs in building interfaith solidarity through health and funeral financing. This research is a qualitative study with data collection techniques of participant observation and in-depth interviews, using social solidarity theory analysis in responding to universal human needs and how individuals play an active role in the creation of social solidarity for people who have different beliefs in it.  The results showed that through the kanyaah fund walking program, social solidarity was created in maintaining a life that upholds tolerance and harmonization in Sukamulya Village.